Effects of medium chain fatty acids and their ability to replace ZnO in weanling pig diets - Rikand, Lauren K.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
The objective of this study was to test the effects of medium chain fatty acids compared to standard ZnO or carbadox in diets for weanling pigs. A total of 360 weanling pigs of 21 days of age were used in a 35-day growth study. Pigs were weaned on day 0 of the experiment in a completely randomized design with a total of 6 dietary treatments being used. The diets are as follows: 1) control; 2) 3,000 ppm ZnO in Phase 1 and 1,500 ppm in Phase 2; 3) 50 g/ton carbadox; 4) 1% blend of C6:C8:C10; 5) 1% Feed Energy 2 (Feed Energy Corp, Des Moines, IA); 6) 1% FORMI (ADDCON, Bitterfeld-Wolfen, Germany). Phases 1 and 2 of the diets were fed from initial weaning to day 19, and a common phase 3 diet was fed from day 20 to 35. During the treatment period, pigs fed ZnO or carbadox had greater (P<0.05) ADG than the R2 or control diets. Pigs fed C6:C8:C10 or FORMI had similar (P>0.05) ADG results as the carbadox treatment. During phase 3, pigs initially fed ZnO had higher (P<0.05) ADG than those fed R2, with the other treatments performing intermediately between the two treatments. There was little impact of G:F (P=0.078) during treatment phases. In conclusion, pigs on the ZnO or carbadox diets performed better than pigs on the MCFA diets when maximizing growth performance. Alternatives such as FORMI resulted in similar growth performance, but more research is needed on MCFA’s in order to replace ZnO or other similar antibiotics in pork production.
Keywords: Spring 2019